Mediterranean connections maritime transport containers and seaborne trade in the Bronze and Iron ages - Knapp, Arthur Bernard 1941-; Demesticha, Stella ca. 20./21. Jh (Routledge, Taylor & Francis Group, 2017)
"This volume focuses on the origin and development of the maritime transport container from the Early Bronze through early Iron Age periods (ca. 3200-700 BC). This category of objects gives us a better understanding of ancient Mediterranean interregional connections, including the roles that shipwrecks, seafaring, and coastal communities played in interaction and exchange. These containers have often been the subject of specific and detailed pottery studies, but have seldom been examined as central to understanding connectivity and trade in the Aegean and eastern Mediterranean. This broad study: considers the likely origins of these types of vessels; traces their development and spread throughout the Aegean and eastern Mediterranean as archetypal organic bulk cargo containers; discusses the wider impact on Mediterranean connections, transport, and trade over a period of 2500 years covering the Bronze and early Iron Ages. Classical and Near Eastern archaeologists and historians, as well as maritime archaeologists, will find this extensively researched volume an important addition to their library"--Provided by publisher